Numerical modelling of CFRP internally reinforced glulam beams - Glišović, Ivan; Todorović, Marija; Simović, Nađa; Pavlović, Marko (Građevinski materijali i konstrukcije, 2025)
Numerous studies have proven that timber structures can be effectively reinforced using fibre-reinforced polymer (FRP) composites. In this paper a nonlinear finite element model was developed to predict bending behaviour of glulam beams reinforced with carbon fibre reinforced polymer (CFRP) plates strategically located in the tension zone between the bottom two laminations. The developed model was validated through comparison with the results of experimental tests for both unreinforced and reinforced beams. To accurately simulate the mechanical behaviour of hybrid glulam-CFRP members, suitable constitutive relations for each material were utilised in the model. The theory of anisotropic plasticity was implemented to include plastic behaviour of timber laminations in the compression zone. The Hill's criterion for orthotropic materials was used as a condition for transition to the plastic state. The progressive damage model was introduced to effectively simulate softening behaviour of timber in tension. The FEM results have shown excellent agreement with the experimental results. Nonlinear behaviour of glulam beams internally reinforced with CFRP was achieved in the numerical analysis, demonstrating the accuracy of developed model past the linear-elastic range.